2011
DOI: 10.3354/meps09356
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic effects of Baltic Sea spring bloom dinoflagellates on co-occurring phytoplankton

Abstract: Dinoflagellate-dominated spring blooms are globally uncommon, but they regularly occur and are even increasing in the Baltic Sea, varying interannually in importance with diatomdominated blooms. The success of dinoflagellates in the spring phytoplankton community has remained poorly understood, as they are expected to be inferior competitors due to their low growth rates and nutrient uptake capacities under nutrient-replete spring conditions. To prevail in the phytoplankton community, dinoflagellates must eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Dinoflagellates have been shown to possess compensatory strategies to compete with fast-growing phytoplankton groups, such as allelopathy, mixotrophy, and internal nutrient storages (Legrand and Carlsson, 1998;Collos et al, 2004;Tillmann et al, 2008). B. baltica has recently been confirmed to effectively suppress growth of co-occurring diatoms by excretion of allelochemicals (Suikkanen et al, 2011), and utilization of residual P has been suggested to facilitate sustained growth of B.baltica in the 2004 mesocosms (Kremp et al, 2008).…”
Section: Dominance Patterns In Experimental Communitiesmentioning
confidence: 99%
“…Dinoflagellates have been shown to possess compensatory strategies to compete with fast-growing phytoplankton groups, such as allelopathy, mixotrophy, and internal nutrient storages (Legrand and Carlsson, 1998;Collos et al, 2004;Tillmann et al, 2008). B. baltica has recently been confirmed to effectively suppress growth of co-occurring diatoms by excretion of allelochemicals (Suikkanen et al, 2011), and utilization of residual P has been suggested to facilitate sustained growth of B.baltica in the 2004 mesocosms (Kremp et al, 2008).…”
Section: Dominance Patterns In Experimental Communitiesmentioning
confidence: 99%
“…, Hattenrath‐Lehmann and Gobler , Suikkanen et al. ), and are influenced by abiotic (e.g., light, temperature, nutrient availability) and biotic (e.g., growth stage, presence or absence of bacteria) factors (Kubanek et al. , Granéli et al.…”
mentioning
confidence: 99%
“…Much of what we know about allelopathy in phytoplankton comes from studies on harmful species (e.g., Arzul et al 1999, Schmidt and Hansen 2001, Kubanek et al 2005, Tang and Gobler 2010. These studies illustrate the complex nature of these interactions, showing that both production of and responses to allelopathic compounds vary greatly between and within species (Gran eli et al 2008, Poulson et al 2010, Hattenrath-Lehmann and Gobler 2011, Suikkanen et al 2011, and are influenced by abiotic (e.g., light, temperature, nutrient availability) and biotic (e.g., growth stage, presence or absence of bacteria) factors (Kubanek et al 2005, Gran eli et al 2008, Prince et al 2008a, Poulson et al 2010, Yamasaki et al 2011. Cell concentrations of both the allelopathic species and its "targets," as well as the duration of exposure to exudates, appear to play important roles in determining outcomes of allelopathic interactions, suggesting that the responses are dose-dependent (Tillmann et al 2007, Poulson et al 2010, Tang and Gobler 2010.…”
mentioning
confidence: 99%
“…With optimal salinity (6 to 20) and temperature (0uC to 6uC) ranges (Kremp et al 2005) and massive resting cyst production (Kremp and Heiskanen 1999;Olli and Trunov 2010), it is well adapted to the Baltic Sea spring bloom conditions. The recently described Gymnodinium corollarium Sundströ m, Kremp & Daugbjerg (Sundströ m et al 2009) dominates the spring bloom in the open Baltic Proper, but also inhabits coastal waters in the northern Baltic Proper (Suikkanen et al 2011). Scrippsiella hangoei (Schiller) Larsen is a minor component of the spring bloom.…”
mentioning
confidence: 99%